Obstacles in Learning Essay Writing: The Perspective of English Foreign Language Learners in Indonesia - Ahmad, Arimuliani; Afrizal, Johari; Mukhaiyar,; Atmazaki, (International Journal of Psychosocial Rehabilitation, 2020)
A crucial aspect of English proficiency that should get enormous attention to lecturers for EFL learner in higher education is essay writing skill. It seems almost of courses expect students to be able to write essays properly but it also becomes a challenge for the learners to be mastered. The purposes of this study were to determine the obstacles faced and the dominant obstacle by EFL students in writing essay. This study was qualitative research with case study design. The participants of this study were 50 university students of third semester in one of private university in Indonesia during academic year 2018-2019. The data were collected by using questionnaire and documentation. The result showed that students face few obstacles in writing essay due to grammatical, organization, spelling, punctuation, capitalization, confusion on supporting idea and word choice. Firstly, the dominant obstacle in grammatical part is the students waste a lot of time to use correct tenses in correct context with 94% of student’s total number admit it. Secondly, for word choice, 86% of student’s total number admit that they face obstacle in modify the word so that they prefer to use simple word rather than phrases in their writing. Thirdly, 72% of student’s total number admit that they face problems in constructing the words in making supporting the ideas. Fourthly, for spelling part, 68% of student’s total number admit that they reviewed their writing and checked their spelling before they submit their writing but their essay indicated few errors of spelling. Sixthly, 66% of students’ total number confuse to add correct punctuation into their essay. Seventhly, for capitalization, 66% of student’s total number often forget to put capitalization after full stop. Moreover, the most dominant problem that admitted by the students is grammatical problem. The findings may give valuable implication to English language lecturers as understanding students’ obstacles in learning English as foreign language and providing appropriate effective teaching and media.